HYDROGEOLOGIC MODELING OF SUBMARINE GROUNDWATER DISCHARGE: COMPARISON TO OTHER QUANTITATIVE METHODS - Oberdorfer J.A. (My University, 2003)
Submarine groundwater discharge (SGD) is approached differently by terrestrial hydrogeologists and marine scientists, including whether to incorporate recirculated seawater with freshwater in the definition. This paper focuses on the major hydrogeologic modeling/calculational methods, what component of SGD they quantify and on what scale. It then compares the modeling methods to direct measurement and geochemical techniques used by marine scientists. Hydrogeologic modeling methods focus primarily on freshwater, but recirculated seawater can be examined with density-dependent, solute transport numerical modeling. Direct physical measurements and geochemical tracers performed in the marine environment can quantify fresh, brackish, or seawater fluxes, so that they are not always comparable to the results of modeling. Because of differences in the geochemistry (nutrients and other dissolved species) of fresh and saline waters, for many applications it may be necessary to distinguish between the fresh and recirculated seawater components of SGD.